Shotgun metagenome guided exploration of anthropogenically driven resistomic hotspots within Lonar soda lake of India - Chakraborty, Jaya; Sapkale, Vibhavari; Rajput, Vinay; Shah, Manan; Kamble, Sanjay; Dharne, Mahesh (Ecotoxicology and Environmental Safety, 2020)
Anthropogenic activities mediated antibiotic resistance genes (ARGs) in the pristine aquatic bodies (lakes) is raising concern worldwide. Long read shotgun sequencing was used to assess taxonomic diversity, distribution of ARGs and metal resistance genes (MRGs) and mobile genetic elements (MGEs) in six sites within hypersaline Lonar soda lake (India) prone to various anthropogenic activities. Proteobacteria and Euryarchaeota were dominant phyla under domain Bacteria and Archaea respectively. Higher abundance of Bacteroidetes was pragmatic at sites 18LN5 and 18LN6. Functional analysis indicated 26 broad-spectrum ARGs types, not reported earlier in this ecosystem. Abundant ARG types identified were multidrug efflux, glycopepetide, bacitracin, tetracycline and aminogylcoside resistance. Sites 18LN1 and 18LN5 depicted 167 and 160 different ARGs subtypes respectively and rpoB2, bcrA, tetA(48), mupA, ompR, patA, vanR and multidrug ABC transporter genes were present in all samples. The rpoB2 gene was dominant in 18LN1, whereas bcrA gene in 18LN2-18LN6 sites. Around 24 MRGs types were detected with higher abundance of arsenic in 18LN1 and copper in 18LN2-18LN6, signifying metal contamination linked to MRGs. The bacterial taxa Pseudomonas, Thioalkalivibrio, Burkholderia, Clostridium, Paenibacillus, Bacillus and Streptomyces were significantly associated with ARGs. This study highlights the resistomic hotspots in the lake for deploying policies for conservation efforts.
Keywords: ARGs; diversity; Lonar lake; MGEs; MRGs; Nanopore sequencing

Spatio-temporal resolution of taxonomic and functional microbiome of Lonar soda lake of India reveals metabolic potential for bioremediation - Chakraborty, Jaya; Rajput, Vinay; Sapkale, Vibhavari; Kamble, Sanjay; Dharne, Mahesh (Chemosphere, 2021)
<span style="color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Lonar Lake, India; a hypersaline and hyperalkaline extremophilic ecosystem having a unique microbial population has been rarely explored for bioremediation aspects. MinION-based shotgun sequencing was used to comprehensively compare the microbial diversity and functional potential of xenobiotic degradation pathways with seasonal changes. Proteobacteria and Firmicutes were prevalent bacterial phyla in the pre-monsoon and post-monsoon samples. Functional analysis from SEED-subsystem and KEGG database revealed 28 subsystems and 18 metabolic pathways for the metabolism of aromatic compounds and xenobiotic biodegradation respectively. Occurrence of N-phenyl alkanoic, benzoate, biphenyl, chloroaromatic, naphthalene, and phenol degradation genes depicted varied abundance in the pre-monsoon and post-monsoon samples. Further, KEGG analysis indicated nitrotoluene degradation pathway (ko00633) abundant in post-monsoon samples, and the benzoate degradation pathway (ko00362) predominant in 19LN4S (pre-monsoon) than 18LN7S (post-monsoon) samples. The abundant genes for benzoate degradation were pcaI: 3-oxoadipate CoA-transferase, alpha subunit, pcaH: protocatechuate 3,4-dioxygenase, beta subunit, and pcaB: 3-carboxy-cis, cis-muconate cycloisomerase, and 4-oxalocrotonate tautomerase. This metagenomic study provides a unique blueprint of hitherto unexplored xenobiotic biodegradation genes/pathways in terms of seasonal variations in the Lonar Lake, and warrants active exploitation of microbes for bioremediation purposes.

Synthesis of advanced asbestos-free material using rice husk ash and marble waste for thermal insulation applications - Verma, Sarika; Bajpai, Harsh; Suresh, S.; Mili, Medha; Gupta, Ritesh Kumar; Shetty, Rohit; Kamble, Sanjay; Khan, Mohd. Akram; Hashmi, S. A. R.; Srivastava, A. K. (Biomass Conversion and Biorefinery, 2023)
The importance and utilization of advanced thermal insulating materials increase due to their broad and irreplaceable energy conservation role. This paper describes the novel way of achieving insulating material. In two waste by-products, namely rice husk ash (RHA), agriculture waste, and marble waste powder (MWP), industrial waste has been utilized to make asbestos-free advanced material for thermal insulation. A novel method for making asbestos-free advanced material for thermal insulation using RHA and marble waste's inherent characteristics has developed mechano-chemical for appropriate physico-chemical consolidation, densification, and ceramic processing route. The Si and Ca sources undergo a series of chemical transformations accompanied by mass transfer and thermal reactions during the synthesis process. The formation of this silicate compound occurs due to the presence of higher contents of CaO in marble waste powder (MWP) and silica in rice husk ash (RHA), resulting in thermal insulating characteristics in the advanced thermal insulation material (ATIM). Raman spectra of ATIM after heating at 1100 degrees C were mainly amorphous, which had a broad peak at 1072 cm(-1). This shows thermal transformation occurs after the heating process, the admixture of tailored powder, and fly ash (FA). The density of the ATIM is found to be 1150 kg/m(3). The phase transformation (glass transition temperature) was found in all the samples between 600 and 800 degrees C. The mechanical properties, namely the compressive strength and impact strength evaluation test, showed that the material meets the standard specifications for ceramic tiles. The thermal conductivity (W/mK) was calculated from different temperature 30, 50, 100,150, and 200 degrees C and found to be 0.571, 0.541, 0.516, 0.498, and 0.477, respectively. According to the test results, it is concluded that ATIM from MWP, RHA, and FA were excellent insulating components. The novel feature of the reported process is the development of non-toxic and asbestos-free thermal insulating low-cost material wherein chemically designed and mineralogically formulating desired phases lead to the homogeneous and effective thermal insulating matrix. The process is feasible, simple, cheap, and highly energy-efficient, increases production efficiency, and is environmentally friendly. The widespread use of advanced material for a broad application spectrum ranges from aerospace, automobile, electronics, transportation, construction, to other industries.
Keywords: Asbestos; Fly ash; Marble waste; Material; Rice husk ash; Thermal insulation

Solvent-assisted chemical recycling of polycarbonate using glycerol as a renewable chemical: mechanistic insights and statistical optimization - Markandeya, Nishant; Jadhav, Mayur; Gopale, Prafulla; Ramalingam, Karthick; Kamble, Sanjay (Process Safety and Environmental Protection, 2026)
The rapid accumulation of polycarbonate (PC) waste has driven the development of efficient recycling methods. This study presents a comprehensive investigation of solvent-assisted chemical recycling of PC using glycerol, a renewable chemical derived from industrial waste streams. Solvent screening highlighted the critical influence of solvent properties such as dielectric constant, dipole moment and hydrogen-bond accepting ability on depolymerization efficiency. A systematic approach combining Design of Experiments (DoE) and Response Surface Methodology (RSM) was employed to optimize the depolymerization process. Using a Box-Behnken design (BBD), the effects of key process parameters, including temperature, reaction time and the glycerol (GLY:PC) and dimethylformamide (DMF:PC) weight ratios, were evaluated in terms of PC conversion and bisphenol A (BPA) yield. The optimization model predicted that a reaction temperature of 171 degrees C, a reaction time of 1 h and a PC: GLY:DMF ratio of 1:5.05:7.22 would yield 100 % PC conversion and 85 % BPA yield. Experimental validation under these conditions achieved 100 % PC conversion and 83 % BPA yield, confirming the reliability of the model. Product characterization using NMR, LC-HRMS and FTIR confirmed the purity of BPA and provided insights into the reaction mechanism. The solvent recyclability across successive reaction cycles demonstrated the environmental and economic viability of the process. Overall, the energy demand calculation based on the environmental energy impact factor (xi) highlights the industrial relevance of this work and demonstrate an efficient and environmentally friendly catalyst-free route for depolymerization of polycarbonate with strong potential for industrial implementation.
Keywords: Chemical Recycling; Glycerol; Polycarbonate; Response surface methodology